Reminiscences of Clyde D. Wagoner : 1950 ... (Columbia University, 2020)
Early accomplishments at WGY, Schenectady; balloon and airplane races; Byrd Antarctic expeditions; recollections of Franklin D. Roosevelt and Henry Ford ...